Electrochemical Behaviour of Quinaldic Acid at Dropping Mercury Electrode and Hanging Mercury Drop Electrode - RAVI KUMAR, Y.; YADAGIRI SWAMY, P.; VEERABHADRAM, G. (Asian Journal of Chemistry, 2010)
The polarographic and cyclic voltammetric studies of quinaldic acid are made at dropping mercury electrode and hanging mercury drop electrode in buffer solutions of various pH values. The polarographic half wave potentials and cyclic voltammetric peak potentials are shifted to more negative values, whilst limiting currents and peak currents are found to decrease with the increase in the pH of the buffer solution. The polarographic wave and cyclic voltammetric peaks are found to be irreversible and diffusion controlled. The values of kinetic parameters are computed using Meites-Israel method.